2018
DOI: 10.1080/03008207.2018.1484916
|View full text |Cite
|
Sign up to set email alerts
|

Short time insulin treatment post burn improves elastic-collagen rearrangement and reepithelization

Abstract: Extensive burn may cause acute resistance to insulin, which accentuates hypermetabolism, impairs glucose metabolism, immune dysfunction and risks of sepsis. To minimize these effects, insulin is used as a treatment. The purpose was to analyze the collagen-elastic arrangement effects of insulin on the burned skin. Wistar rats were assigned in groups: control (C); control with insulin (C + I); scald burn injury (SBI); and SBI with insulin (SBI+ I). SBI were submitted to 45% total body surface area burn and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In a previous study, we reported that topical insulin increased Type I collagen fibers and improved organization and the rate of healing in second-degree burns (Azevedo et al, 2015). Our findings corroborate those of Baptista et al (2018), who observed that scald-burn injuries in diabetic animals improved after 4 days of topical insulin treatment (5 U/kg/day) due to the rearrangement of elastic−collagen fibers rearrangement and reepithelization of injured tissue. Taken together, these data confirm the capacity of topical insulin to modulate components of the extracellular matrix, leading to increased speed of wound closure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a previous study, we reported that topical insulin increased Type I collagen fibers and improved organization and the rate of healing in second-degree burns (Azevedo et al, 2015). Our findings corroborate those of Baptista et al (2018), who observed that scald-burn injuries in diabetic animals improved after 4 days of topical insulin treatment (5 U/kg/day) due to the rearrangement of elastic−collagen fibers rearrangement and reepithelization of injured tissue. Taken together, these data confirm the capacity of topical insulin to modulate components of the extracellular matrix, leading to increased speed of wound closure.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, it is among the promising treatments for burn wounds among patients with diabetes (Hrynyk & Neufeld, 2014; Lima et al, 2012; Oryan & Alemzadeh, 2017; Wu et al, 2009). Studies have shown that, compared to burn wounds in patients with diabetes not treated with insulin, those treated with insulin have faster closure with a diminished inflammatory phase, improved formation of granulation tissue, and collagen fibers organized in meshes in a characteristic pantographic pattern similar to healthy skin (Azevedo et al, 2015; Baptista et al, 2018; Hrynyk & Neufeld, 2014; Oryan & Alemzadeh, 2017). The mechanism by which insulin enhances the rate of wound healing in patients with diabetes, however, is not completely understood.…”
mentioning
confidence: 99%
“…Our research group found improvement in elastic-collagen rearrangement and reepithelization in short-term insulin treatment when comparing short-and long-term insulin treatments in burn-injured skin. 25 However, in this study, we investigated the effects of insulin treatment on a muscle distant from extensive burn lesion. Regarding experimental studies on extensive BIs and intensive insulin therapy, most authors studied short-term therapy acting in the acute postburn phase, ranging from 1 to 5 d. [30][31][32][33][34][35][36] Few Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The insulin dosage used was chosen based on studies whose authors administered insulin treatment in euglycemic murine models. 24,25 Insulin-treated rats received 5% sucrose in drinking water to maintain euglycemia. 26 The weight and water and food intake of all animals were recorded every day since weaning, which included the days of adaptation in individual cages.…”
Section: Scald Burn Injury and Insulin Treatmentmentioning
confidence: 99%
“…Collagen is an extracellular fibrin that promotes the formation of the intracellular matrix and repair of damaged cell structures ( 31 ). Type I and III collagen are the major components of collagen in the ECM and serve a major role in wound healing ( 32 ). The results of the present study demonstrated that miR-27b inhibition significantly upregulated the mRNA and protein expression of collagen I and III in scalded skin tissues of rats and in BJ cells, which may be associated with the accelerated healing of scalded skin in rats.…”
Section: Discussionmentioning
confidence: 99%